Soft computing in data science : second International Conference, SCDS 2016, Kuala Lumpur, Malaysia, September 21-22, 2016, Proceedings /: second International Conference, SCDS 2016, Kuala Lumpur, Malaysia, September 21-22, 2016, Proceedings. (2016) - Unknown
No abstract available